Colonial architecture on local history through glass sculpture / Mahizan Hijaz Mohammad and Aznan Omar - Hijaz Mohammad, Mahizan; Omar, Aznan (Universiti Teknologi MARA, Perak, 2021)
The aim of this paper is to study the aspect of colonial building that relates to local history. The history of tin mining is to be acknowledged and understand as important to the local. Local history has been part of important aspect in a developing community. It signifies engagement of the link between the present and the past. It helps the community to learn about the events that has happened and in the Malaysian context, the history of the British colonial is the most relevant for it is visibility due to the architectural ruin that is on location. The method applied is Critical Self reflections and studio experimentation. Samples and images of location on site retrieved to study the visual aspect of the buildings and applied as part f the artwork. Artwork explorations are conducted to relate the material and techniques to the context of the study. The British occupation existed in Malaysia for more than two hundred years from 1795 until 1957. In Malaysia generally there are four typical colonial styles of architecture which are Moorish, Tudor, Neo Classic and Neo Gothic (A Ghafar Ahmad, 1997). The tin mining industry has brought merchant and workers to Central Perak such as Gopeng and Batu Gajah. According to (Syed Zainol Abidin Ibid,1995), during 1900 till 1940s, there are three architectural style that influenced the construction of commercial building and shop houses which are adaptation style, eclectic and Art Deco. However, after time the Colonial buildings have decayed and turn into ruins. The beauty and style of the Colonial architecture has inspired the researcher to study the building since it is visible in the surrounding central Perak and keeps an interesting story of the past. Working with glass, the researcher will fabricate the idea of colonial building and glass as a work of art.